Augmented Reality: Fundamentals and Applications - Vergara Villegas, Osslan Osiris (CRC Press Taylor and Francis Group, 2024)
https://www.routledge.com/Augmented-Reality-Fundamentals-and-Applications/VergaraVillegas-CruzSanchez/p/book/9781003435198